Solitary Fibrous Tumor of the Prostate Which Was Initially Misdiagnosed as Prostate Cancer. (26th February 2017) - Osamu, Soma; Murasawa, Hiromi; Imai, Atsushi; Hatakeyama, Shingo; Yoneyama, Takahiro; Hashimoto, Yasuhiro; Koie, Takuya; Ohyama, Chikara
Abstract : Solitary fibrous tumor (SFT) of the prostate is a very rare tumor. We report a case of 65-year-old man with SFT of the prostate which was initially misdiagnosed as prostate cancer. Finally, we performed total prostatectomy and the tumor was histologically diagnosed as SFT of the prostate. The patient's clinical course has progressed favorably with no obvious recurrence 18 months postoperatively.